Biophysical Characteristics of the Mount Hamiding Protected Forest Area and Forest Engineering for Sustainability - Maatoke, Cornelia Dolfina; Kailola, Jacob (Agrikan Jurnal Agribisnis Perikanan, 2025)
The purpose of this study was to determine the biophysical conditions of the protected forest area of Mount Hamiding: soil, slope, climate and sustainable management strategies. The method used in this study is a descriptive method with a qualitative-quantitative approach. Data collection techniques were carried out using observation, interview and literature study techniques. The results of the study showed that the biophysical conditions of the protected forest area of Mount Hamiding have slopes from flat to steep, entisol soil types which are newly formed soils with physical and chemical soil properties, while the climate type in the protected forest area is based on climate A and B. Forest and soil damage caused by anthropogenic activities, namely clearing forests to expand agricultural and plantation areas, and illegal logging. Based on this phenomenon, the strategic efforts made to manage forests sustainably, namely to improve the physical and chemical conditions of the soil, are through forest rehabilitation activities with an agroforestry model that aims to improve ecological functions and community welfare because this pattern is a form of product diversification and provides ecological functions for the environment.